TWO-WHEELER CONSUMERS’ BEHAVIOUR TOWARDS CUSTOMER SATISFACTION - Khan, Mohd. Akbar Ali; Rao, Datrika Venkata Madhusudan (International Journal of Research -GRANTHAALAYAH, 2018)
This original exploratory study was to examine the impact of select exogenous and demographic variables on Customer Satisfaction. As per ACMA May month data, top four brands, namely Hero, Bajaj, Honda and TVS brands were selected for study and 600 two-wheeler consumers’ samples collected, using random sampling in Hyderabad. The data were analysed with descriptive statistics, and non-parametric tests, to know the impact of independent and demographic variables on customer satisfaction and found no impact, further given different implications.